2011
DOI: 10.4103/0972-3919.106710
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral axillary lymph node uptake of radiotracer during lower extremity and scrotal lymphoscintigraphy in a case of primary scrotal lymphoedema

Abstract: Lymphoscintigraphy is a useful technique for the evaluation of lymphatic function in the presence of limb swelling. The authors report a case where genital swelling in a 20-year-old man was investigated by lymphoscintigraphy. We performed lower limb lymphoscintigraphy and scrotal lymphoscintigraphy in the patient on two different days. Lower limb revealed dermal backflow pattern in lower limbs, inguinoscrotal reflux of the lymph and unexpected avid radiotracer uptake in the axillae bilaterally. Scrotal lymphos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…This unusual lymphatic drainage pattern may indicate variation and adaptability of lymphatic system to congenital abnormality. Although it is rare, axillary lymph nodes uptake in lower-limb lymphoscintigraphy has been described in patients with different etiologies 7,8 . Our case is unique and first with regard to its etiology with a quite unusual presentation.…”
mentioning
confidence: 68%
See 1 more Smart Citation
“…This unusual lymphatic drainage pattern may indicate variation and adaptability of lymphatic system to congenital abnormality. Although it is rare, axillary lymph nodes uptake in lower-limb lymphoscintigraphy has been described in patients with different etiologies 7,8 . Our case is unique and first with regard to its etiology with a quite unusual presentation.…”
mentioning
confidence: 68%
“…Although it is rare, axillary lymph nodes uptake in lower-limb lymphoscintigraphy has been described in patients with different etiologies. 7,8 Our case is unique and first with regard to its etiology with a quite unusual presentation. Scintigraphic findings may be concluded as recurrence of vulvar lymphangioma circumscriptum accompanying with congenital hypoplasia/aplasia of lymphatics in lower limbs and aberrant lymphatic drainage pattern, possibly due to congenital variation.…”
mentioning
confidence: 79%
“…The differential diagnoses of scrotal lymphangioma presenting as cysts may include hernia, hydrocoele, hematocele, spermatocele, epididymal cyst, and varicocoele 5–7 . In lymphoscintigraphy, focal radioactivity in scrotal region may be due to urine leakage, 8 lymphocele, 9 filariasis, 10 lymphatic fistula, 11 and primary lymphoedema 12 . Revealed by our case, scrotal lymphangioma should also be added to the etiologic list of diffuse scrotal activity in lymphoscintigraphy.…”
mentioning
confidence: 77%
“…[5][6][7] In lymphoscintigraphy, focal radioactivity in scrotal region may be due to urine leakage, 8 lymphocele, 9 filariasis, 10 lymphatic fistula, 11 and primary lymphoedema. 12 Revealed by our case, scrotal lymphangioma should also be added to the etiologic list of diffuse scrotal activity in lymphoscintigraphy. In addition to evaluating the status of lymphatic abnormality, lymphoscintigraphy can also help select appropriate approaches to patient management in different situations.…”
mentioning
confidence: 80%
“…Aberrant lymphatics identified by lymphoscintigraphy have been rarely reported. Jain and Jaimini[ 6 ] have reported a case of congenital hypoplasia of lower limb lymphatics with visualization of bilateral axillary lymph nodes in lower limb and scrotal lymphoscintigraphy without visualization of liver. They concluded that patient had an aberrant lymphatic pathway, possibly secondary to malfunctioning/nonfunctioning thoracic duct.…”
Section: Discussionmentioning
confidence: 99%